Effects of Six Sequential Charged Particle Beams on Behavioral and Cognitive Performance in B6D2F1 Female and Male Mice - Raber, Jacob; Fuentes Anaya, Andrea; Torres, Eileen Ruth S.; Lee, Joanne; Boutros, Sydney; Grygoryev, Dmytro; Hammer, Austin; Kasschau, Kristin D.; Sharpton, Thomas J.; Turker, Mitchell S.; Kronenberg, Amy (Frontiers in Physiology, 2020)
The radiation environment astronauts are exposed to in deep space includes galactic cosmic radiation (GCR) with different proportions of all naturally occurring ions. To assist NASA with assessment of risk to the brain following exposure to a mixture of ions broadly representative of the GCR, we assessed the behavioral and cognitive performance of female and male C57BL/6J x DBA2/J F1 (B6D2F1) mice two months following rapidly delivered, sequential 6 beam irradiation with protons (1 GeV, LET = 0.24 keV, 50%), 4He ions (250 MeV/n, LET = 1.6 keV/m, 20%), 16O ions (250 MeV/n, LET= 25 keV/m 7.5%), 28Si ions (263 MeV/n, LET = 78 keV/m, 7.5%), 48Ti ions (1 GeV/n, LET =107 keV/m, 7.5%), and 56Fe ions (1 GeV/n, LET = 151 keV/m, 7.5%) at 0, 25, 50, or 200 cGy) at 4-6 months of age. When the activity over three days of open field habituation were analyzed in female mice, those irradiated with 50 cGy moved less and spent less time in the center than sham-irradiated mice. Sham-irradiated female mice and those irradiated with 25 cGy showed object recognition. However, female mice exposed to 50 or 200 cGy did not show object recognition. When fear memory was assessed in passive avoidance tests, sham-irradiated mice and mice irradiated with 25 cGy showed memory retention while mice exposed to 50 or 200 cGy did not. The effects of radiation passive avoidance memory retention were not sex-dependent. There was no effect of radiation on depressive-like behavior in the forced swim test. There was a trend towards an effect of radiation on BDNF levels in the cortex of males, but not for females, with higher levels in male mice irradiated with 50 cGy than sham-irradiated. Finally, sequential 6-ion irradiation impacted the composition of the gut microbiome in a sex-dependent fashion. Taxa were uncovered whose relative abundance in the gut was associated with the radiation dose received. Thus, exposure to sequential six-beam irradiation significantly affects behavioral and cognitive performance and the gut microbiome.